INVESTIGATION ON DYNAMIC CHARACTERISTIC OF CYLINDER GEARS AND SIMULATION BASED ON ADAMS - CHENG YanLi; XIAO ZhengMing; WANG Xu (Jixie qiangdu)
Translational-rotational coupling dynamic model of the cylinder gear transmission system was established using the lumped-parameter method,which considered the time-varying mesh stiffness,mesh damping,friction of tooth surface.According to the design parameters,Runge-Kutta was used to get the vibration displacements of each gear and the mesh force of the gear pair. The multi-body contact dynamics model of the gear transmission system was built based on ADAMS,and dynamic mesh forces and vibration displacement and vibration velocity were obtained by the simulation. With the test plan,the vibration acceleration of the gear transmission system was measured,and then the velocity and displacement could get by numerical integration to analyze the vibration characteristics. The results show that in terms of gear velocity and displacement,the test data and theoretical analysis results have good consistency,which verify the feasibility of comparative rearch of the two method.